Distribution of lead and mercury in Ontario peatlands. (December 2017) - Talbot, Julie; Moore, Tim R.; Wang, Meng; Ouellet Dallaire, Camille; Riley, John L.
Abstract: While considerable attention has been given to the measurement of mercury (Hg) and lead (Pb) concentrations and accumulation in detailed peat cores in central Canada, the geographic distribution and density of sampling are generally limited. Here, we use the Ontario Peatland Inventory to examine broad patterns of Hg and Pb concentration with depth, based on 338 peat cores (containing >1500 analyzed samples) from 127 bogs, fens and swamps located in southeastern, northeastern and northwestern sections of Ontario. Overall, Hg concentrations averaged 0.05 μg g −1 and that of Pb averaged 10.8 μg g −1 . Maximum values in the top 50 cm of the profiles are 0.08 μg g −1 and 26.2 μg g −1 for Hg and Pb, respectively. The ratio between these values (surface) and the values from below 100 cm (background), where peat likely accumulated before 1850 and industrial activities were limited, are 2.3 and 6.6 for Hg and Pb, respectively. The highest surface:background concentration ratios are generally found in the westernmost part of the province and in the southeast for Hg and around areas that are more heavily populated for Pb. Our results show that a vast amount of Hg and Pb are stored in Ontarian peatlands, although the spatial distribution of these stores varies. The rapid decomposition of peat in a changing climate could release these pollutants to the atmosphere. Graphical abstract: Highlights: Peatlands can record traces of atmospheric pollution. Hg and Pb concentrations increase in the upper portion of 338 peat profiles sampled within a 450 000 km 2 area in Ontario. The magnitude of increase varies geographically, Hg and Pb showing different patterns. Abstract : Ontario peatlands store a considerable amount of lead and mercury, especially in the peat accumulated since industrialization. This storage is spatially variable.